Vertically integrated diffractive gratings on photonic crystal surface emitting lasers - Lih-Ren Chen (Nature Portfolio, 2021)
Abstract We designed and fabricated a photonic crystal surface emitting laser (PCSEL) with vertically integrated diffractive optical elements on their top to study the mechanism of static beam steering on a single chip. The deflected output beam by the self-formed periodic ITO cladding layer of the PCSEL can be further steered by changing the grating period and azimuthal angle of the diffractive gratings relative to the photonic crystal. Through the analysis of photonic band structure and lasing characteristics, the periodic ITO structure is coupled to the photonic crystal band, whereas the integrated grating serves the diffractive function only. The findings pave the way for the design of PCSELs enabling single or multiple output beam with varying direction capability. This type of laser is regarded as an ideal light source for various applications, such as light detection and ranging and three-dimensional sensing systems.